Associations between homocysteine and B vitamins and stroke: a cross-sectional study - Zhang, Panpan; Xie, Xia; Zhang, Yurong (Frontiers in Neurology, 2023)
Objective: Homocysteine (Hcy) is a predictor for stroke. B vitamins are required for the metabolism of Hcy. We designed a study to investigate the associations of plasma Hcy and B vitamins with the prevalence of stroke in adults. Methods: A total of 8,371 adults were included in the National Health and Examination Survey (NHANES) between 2003–2006 in the United States. Multivariate regression analysis and smooth curve fitting were conducted to evaluate the associations of stroke prevalence with Hcy, folate, vitamin B6, and B12. A segmented regression model was used to analyze the threshold effects. Sample weights were calculated to ensure the results' generalizability. Results: The mean age of all participants was 46.43 years (51.8% women), and the prevalence of stroke was 2.72%. A nonlinear and positive association was found between plasma Hcy levels and the prevalence of stroke. Furthermore, L-shaped associations were found between plasma vitamin B6 and folate levels and stroke, with the turning points at 65.2 nmol/L for vitamin B6 and 26 nmol/L for folate, respectively. Vitamin B12 revealed a U-shaped relationship with stroke, with the turning points at 492.98 pmol/L for vitamin B12. Conclusion: Non-linear associations of plasma Hcy and B vitamins levels with stroke prevalence were found in American adults. These associations may have an implication that higher plasma Hcy levels should be reduced, and plasma vitamin B6, vitamin B12 and folate levels should be moderately improved in stroke prevention. Future studies are needed to verify the causality of these associations and elucidate the underlying mechanisms.